The Human Gene SLC25A29, of Solute Carrier Family 25, Encodes a Mitochondrial Transporter of Basic Amino Acids - Porcelli, Vito (American Society for Biochemistry and Molecular Biology, 2014)
The human genome encodes 53 members of the solute carrier family 25 (SLC25), also called the mitochondrial carrier family, many of which have been shown to transport carboxylates, amino acids, nucleotides, and cofactors across the inner mitochondrial membrane, thereby connecting cytosolic and matrix functions. In this work, a member of this family, SLC25A29, previously reported to be a mitochondrial carnitine/acylcarnitine- or ornithine-like carrier, has been thoroughly characterized biochemically. The SLC25A29 gene was overexpressed in Escherichia coli, and the gene product was purified and reconstituted in phospholipid vesicles. Its transport properties and kinetic parameters demonstrate that SLC25A29 transports arginine, lysine, homoarginine, methylarginine and, to a much lesser extent, ornithine and histidine. Carnitine and acylcarnitines were not transported by SLC25A29. This carrier catalyzed substantial uniport besides a counter-exchange transport, exhibited a high transport affinity for arginine and lysine, and was saturable and inhibited by mercurial compounds and other inhibitors of mitochondrial carriers to various degrees. The main physiological role of SLC25A29 is to import basic amino acids into mitochondria for mitochondrial protein synthesis and amino acid degradation.